2013
DOI: 10.1371/journal.pone.0069497
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Capture Misleads about Ecological Speciation in the Daphnia pulex Complex

Abstract: The North American ecological species Daphnia pulicaria and Daphnia pulex are thought to have diverged from a common ancestor by adaptation to sympatric but ecologically distinct lake and pond habitats respectively. Based on mtDNA relationships, European D . pulicaria is considered a different species only distantly related to its North American counterpart, but both species share a lactate dehydrogenase (Ldh) allele F supposedly involved in lake adaptation in North America, and the same allele is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 62 publications
(120 reference statements)
4
60
0
Order By: Relevance
“…Our results suggest that further investigation are advisable in order to verify whether the current population is the last remnant of a once much larger metapopulation eventually reduced by anthropogenic disturbances (e.g., fish introductions, water contamination with toxic chemicals) or if it represents the invasion of North American strains that have recently colonised large parts of New Zealand, Africa and Spain, and that was already recorded in Northern Italy and Sardinia (Mergeay et al, 2006; Vergilino et al, 2011;Duggan et al, 2012;Crease et al, 2012;Markova et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results suggest that further investigation are advisable in order to verify whether the current population is the last remnant of a once much larger metapopulation eventually reduced by anthropogenic disturbances (e.g., fish introductions, water contamination with toxic chemicals) or if it represents the invasion of North American strains that have recently colonised large parts of New Zealand, Africa and Spain, and that was already recorded in Northern Italy and Sardinia (Mergeay et al, 2006; Vergilino et al, 2011;Duggan et al, 2012;Crease et al, 2012;Markova et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The identity of European and American populations of morphologically similar species may be doubtful (Hrbacek, 1987). The accumulation of genetic data has showed that North American and European D. pulex are genetically two distinct species and nomenclature of the D. pulex complex is not resolved (Colbourne et al, 1998;Palsoon, 2000;Mergeay et al, 2006;Petrusek et al, 2008;Crease et al, 2012;Markova et al, 2013). Even in Europe, asexual strains of D. pulex show a more northerly distribution than sexual ones (Ward et al, 1994;Weider and Hobaek, 1997) and both lineages may co-exist within the same geographical region (Letho and Haag, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To characterize the interactions of organisms with their environment at molecular level, genomics studies genetic material recovered directly from environmental samples, proteomic addresses protein localization and functional cataloguing, and metabolomics assesses organism function and health through metabolites dynamics. Methods frequently include using microsatellites to determine gene flow and hybridization between populations (Colautti et al, 2005;Vergilino et al, 2011;Marková et al, 2013). The development of molecular ecology is also closely related to the use of DNA microarrays, which allows for the simultaneous analysis of the expression of thousands of different genes.…”
Section: Molecular Ecologymentioning
confidence: 99%
“…The presence of the predaceous larvae of Chaoborus flavicans probably account for seasonal variation of juveniles morphology that showed neckteeth and/or elongated tail spines as typical predator- (Rossi et al, 2014). Recently, the invasive hybrid lineage of the American D. pulex and American D. pulicaria, invaded Africa and was already recorded in Northern Italy and Sardinia (Mergeay et al, 2006;Fadda et al, 2011;Marková et al, 2013). In this study, we used a diagnostic mitochondrial DNA gene to identify if D. pulex population from Bodrio del pastore III represents this invasive hybrid clone or if it belongs to native European D. pulex strain.…”
Section: Introductionmentioning
confidence: 99%